IgE Epitopes of the House Dust Mite Allergen Der p 7 Are Mainly Discontinuous and Conformational - Curin, Mirela; Huang, Huey-Jy; Garmatiuk, Tetiana; Gutfreund, Sandra; Resch-Marat, Yvonne; Chen, Kuan-Wei; Fauland, Kerstin; Keller, Walter; Zieglmayer, Petra; Zieglmayer, René; Lemell, Patrick; Horak, Friedrich; et al. (Frontiers in Immunology, 2021)
Background: Several studies indicate that Der p 7 is an important and clinically relevant allergen of Dermatophagoides pteronyssinus which should be included in vaccines for treatment of house dust mite (HDM) allergy. Aim of this study was to characterize the IgE epitopes of Der p 7. Methods: Recombinant Der p 7 was expressed and purified, analysed for fold by circular dichroism and tested for its allergenic activity by basophil activation. Seven overlapping, surface-exposed peptides (P1-P7) with a length of 27-37 amino acids, that spanned the Der p 7 sequence were synthesized and tested for IgE reactivity and allergenic activity by basophil activation assay. Carrier-bound peptides were studied for their ability to induce allergen-specific IgG antibodies in rabbits. Peptide-specific antibodies were used to inhibit allergic patients` IgE binding to Der p 7 by ELISA for mapping of IgE epitopes. Results: rDer p 7 showed high allergenic activity comparable with Der p 5, Der p 21 and Der p 23. None of the seven tested peptides showed any IgE reactivity or allergenic activity when tested with HDM- allergic patients indicating lack of sequential IgE epitopes on Der p 7. IgE inhibition experiments using anti-peptide specific IgGs and molecular modelling enabled us to identify discontinuous, conformational IgE epitopes of Der p 7. Conclusion and clinical relevance: IgE epitopes of Der p 7 belong to the conformational and discontinuous type whereas sequential Der p 7 peptides lack IgE reactivity. It should thus be possible to construct hypoallergenic vaccines for Der p 7 based on carrier-bound allergen peptides.